Perbandingan Metode Tuning PID pada Pengaturan Kecepatan Parallel Hybrid Electric Vehicle - Utama, Yoga Alif Kurnia; Tamaji, Tamaji (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
Parallel Hybrid Electric Vehicle (PHEV) is a type of hybrid vehicle which have a movement power from combination of a combustion motor and an electric motor with a parallel connection. This vehicle is one solution to reduce the use of fossil fuels. This is because fossil fuels used by motorized vehicles are the biggest contributor to air pollution in urban areas. In fact, Europe is targeting as many as 30 million cars to be replaced by electric or hybrid vehicles by 2030. Therefore, research on hybrid vehicles is important. In this research, PID control will be used to adjust the speed of PHEV. This PID will be tuned using Ziegler Nichols (ZN), Cohen Coon (CC), and the Bat Algorithm (BA). The results show that BA is the best tuning method which has better performance compared to other methods. Keyword : Bat Algorithm, PID Tuning, Speed Controller, PHEV